Artikel The Role of Digital Marketing Strategies in Strengthening Modern Businesses for Startups in Medan City - Arief Muhazir Insandi; Tampe Tuah Malem Ginting (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
Digital marketing has become a key component of modern business strategies, particularly for startups facing intense competition and challenges in establishing a strong market presence. This research aims to explore how digital marketing strategies can contribute to the growth and competitiveness of modern businesses, especially startups in Medan City. Utilizing descriptive analysis methods and secondary data from various sources, this study identifies key elements of digital marketing such as social media, search engine optimization (SEO), and digital advertising as effective tools for attracting customers, enhancing brand awareness, and expanding market reach. The analysis results show that digital marketing enables companies to directly interact with customers, provide personalized experiences, and measure campaign effectiveness in real-time. This positively impacts operational efficiency and resource management. In Medan City, startups implementing integrated digital marketing strategies have shown significant growth in customer acquisition and strengthened competitiveness in local and regional markets. In conclusion, digital marketing not only supports the growth of startups but also serves as a differentiating factor enabling them to survive in the digital economy era. This study recommends increased investment in digital marketing technologies and human resource training to ensure the successful implementation of these strategies